MODIFIKASI UKURAN PIZZA ISIAN PASTA SAUS RENDANG DENGAN UKURAN SATU GIGIT - Vino Alex Andro Susanto; Tito Pandu Raharjo (Media Bina Ilmiah, 2024)
Pizza is a food from Italy that has been widely adapted in Indonesia, including innovation with rendang sauce, a traditional Indonesian dish that is rich in flavor. This study aims to identify the factors that influence the texture of one-bite rendang sauce pasta stuffed pizza, as well as measure consumer preference and acceptability of the product. Some of the main ingredients used were high-protein wheat flour, fermipan, olive oil, and various ingredients used to make pasta and rendang sauce. This study used an experimental method with three independent variables: pizza dough type (thick and thin), pasta type (penne and fusilli), and rendang sauce consistency (liquid and thick). 45 untrained panelists were used in this study to rate the products on a hedonic scale for taste, aroma, appearance, texture, and overall quality. The results showed that the combination of thin pizza, penne pasta, and thick rendang sauce (A2B1C2) received the most positive response from the panelists, especially in terms of texture and overall quality. The conclusion of this study is that the most optimal texture on this one-bite rendang sauce pasta stuffed pizza can be achieved by using a combination of thin pizza, and thick rendang sauce.